2020
DOI: 10.2147/oarrr.s238649
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neurological Manifestations in Familial Mediterranean Fever: a Genotype-Phenotype Correlation Study</p>

Abstract: Background and Aims: Familial Mediterranean Fever (FMF) is a periodic autoinflammatory disease with an autosomal recessive hereditary pattern. The aim of this study is to explain the spectrum of possible neurological manifestations and its genotypephenotype correlation in patients with familial Mediterranean fever. Methods: In this case series study, data of 311 FMF patients at the FMF Registration Center in Iran (http://www.fmfiran.ir/) was studied. Patient's information was entered into a researcher designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…Headache was found only in five of our patients which is in contrast with other Iranian and Turkish studies [38,45], while it was detected as a symptom of recurrent meningitis and pseudotumor cerebri and both are present in 9.7 % and 9% of our patients respectively. The presence of pseudotumor cerebri in conjunction with FMF has been described in the literature [46][47][48].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Headache was found only in five of our patients which is in contrast with other Iranian and Turkish studies [38,45], while it was detected as a symptom of recurrent meningitis and pseudotumor cerebri and both are present in 9.7 % and 9% of our patients respectively. The presence of pseudotumor cerebri in conjunction with FMF has been described in the literature [46][47][48].…”
Section: Discussioncontrasting
confidence: 95%
“…Regarding neurological manifestation, vertigo was the most common neurological symptom as it was detected in about 22.8% of the studied patients, followed by paresthesia and seizures. This was in accordance with a recent Iranian publication that detected vertigo in 27.7% of FMF patients and reported it as a common presentation in FMF [38].…”
Section: Discussionsupporting
confidence: 93%
“…[33][34][35] We reported recently neurological manifestation of familial Mediterranean fever as a separate study. 36 FMFassociated central nervous system (CNS) involvement includes demyelinating lesions, stroke, and posterior reversible leukoencephalopathy syndrome (PRES). Different studies showed that MS patients with MEFV mutations seem to develop a more progressive disease and it seems that MEFV mutations may increase the risk of MS progression.…”
Section: Neurological Diseasementioning
confidence: 99%
“…Overall, the heterogeneity in clinical FMF manifestations reflects the changes occurring in the repertoire of mutations. Genotype–phenotype relationships are also important to characterize specific clinical aspects of FMF, such as neurological manifestations [ 47 ].…”
Section: Uncertainty Analysis and Rare Diseasesmentioning
confidence: 99%